Insights on SARS-CoV-2: Emerging Outbreaks of Viral Infections and the Need for Heightening the Antiviral Research - Peraman, Ramalingam; Pemmadi, Raghuveer Varma; Peraman, Muthukumaran; Sure, Sathish Kumar (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Today, about 47 life threatening viruses have been notified for their outbreak potentials including SAR-CoV-2. The proximal origin of SARS-CoV-2 and its affinity to human ACE2 receptors ended in COVID-19 disease pandemic. The genome of SARS-CoV-2 is quite complex and unclear, thus the progress on new antiviral drugs and vaccine discovery is hampered. Worldwide, Indian horizon has emerged as potential source for supply of drugs like hydroxychloroquine, remdesvir, ritonavir lopinavir, etc., to several countries. However, the research initiatives undertaken by Indian industries to fight against COVID-19 are relatively lower than the research attempts of developed countries. Furthermore, Indian industry’s collaboration with scientists of research institutes or universities is also very limited. Therefore, the need for enhancing antiviral research activities in India is highly recommended to combat COVID-19 like pandemic, if arise in future as well. Hypothesis: Being Indian pharma market as one of the top five leading pharma marketer of this globe, the COVID-19 pandemic lessoned us to realize the need for improving the antiviral research among pharmaceutical industries of Indian horizon. It is needed for the hour as measure to sustain the pharma market credibility at globe. Results and Conclusion: In this raising era of viral epidemics, it is imperative that Indian pharmaceutical industries should initiate antiviral research through collaborative approach between pharmaceutical industry and scientists across the globe including researchers from academia and non-profit research organization. Thus, this attempt will definitely improve the antiviral and other drug discovery research initiatives among Indian pharmaceutical industries and will save millions of life from viral pandemics like COVID-19 in near future.
Keywords: Emerging viruses; Antiviral; COVID-19; Pharma industries; Indian Horizon; SARS-CoV-2 genome